Formal total synthesis of (-)-kumausallene - Das, Shyamsundar; Ramana, Chepuri V. (Tetrahedron, 2015)
Deacetylkumausyne-a penultimate intermediate in Tang's total synthesis of (-)-kumausallene has been synthesized employing a chiral pool approach and thus culminating in a formal total synthesis of kumausallene. The opening of an epoxide with alkyne (use of Birch reduction for the selective construction of E-pent-3-enyl group) and C-allylation have been used to introduce the pendant alkenyl side chains. Initial attempts to execute an alternative to Tang's route comprising a prior installation of the bromoallene unit via bromoetherification and subsequent S(N)2 displacement are unsuccessful. To overcome this, an alternative approach was developed to arrive at Deacetylkumausyne (another natural product that has been synthesized and characterized by Tang's group). Thus, this overall exercise has culminated in a formal total synthesis of (-)-kumausallene. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bis-THF natural products; Chiral pool; Deacetylkumausyne; Total synthesis; Wittig reaction

Fluoride-mediated dephosphonylation of α-diazo-β-carbonyl phosphonates - Phatake, Ravindra S.; Mullapudi, Venkanna Babu; Wakchaure, Vivek Chandrakant; Ramana, Chepuri V. (Organic Letters, 2016)
The possibility of fluoride-mediated selective dephosphonylation of α-diazo-β-carbonyl phosphonates such as the Ohira-Bestmann reagent has been proposed and executed. The resulting α-diazocarbonyl intermediates undergo a (3 + 2)-cycloaddition at room temperature with conjugated olefins and benzynes. Interestingly, under the current conditions, the resulting cycloaddition products underwent either N-acylation (with excess α-diazo-β-carbonyl phosphonates) or Michael addition (with conjugated olefins).

Fungal cell membrane-promising drug target for antifungal therapy - Sant, D. G.; Tupe, Santosh Genba; Ramana, Chepuri V.; Deshpande, Mukund V. (Journal of Applied Microbiology, 2016)
Increase in invasive fungal infections over the past few years especially in immunocompromised patients prompted the search for new antifungal agents with improved efficacy. Current antifungal armoury includes very few effective drugs like Amphotericin B; new generation azoles, including voriconazole and posaconazole; echinocandins like caspofungin and micafungin to name a few. Azole class of antifungals which target the fungal cell membrane are the first choice of treatment for many years because of their effectiveness. As the fungal cell membrane is predominantly made up of sterols, glycerophospholipids and sphingolipids, the role of lipids in pathogenesis and target identification for improved therapeutics were largely pursued by researchers during the last few years. Present review focuses on cell membrane as an antifungal target with emphasis on membrane biogenesis, structure and function of cell membrane, cell membrane inhibitors, screening assays, recent advances and future prospects.

Fluoride-mediated dephosphonylation of alpha-diazo-beta-carbonyl phosphonates - Phatake, Ravindra S.; Mullapudi, Venkannababu; Wakchaure, Vivek C.; Ramana, Chepuri V. (Organic Letters, 2017)
The possibility of fluoride-mediated selective dephosphonylation of alpha-diazo-beta-carbonyl phosphonates such as the Ohira-Bestmann reagent has been proposed and executed. The resulting alpha-diazocarbonyl intermediates undergo a (3 + 2)pcycloaddition at room temperature with conjugated olefins and benzynes. Interestingly, under the current conditions, the resulting cycloaddition products underwent either N-acylation (with excess alpha-diazo-beta-carbonyl phosphonates) or Michael addition (with conjugated olefins).